# Derivative of ${ x }^{ x }$ without logarithmic differentiation

With logarithmic differentiation, it is quite simple to compute the derivative of $x^x$:

$$y=x^x$$ $$\ln {y} =x \ln{x}$$ $$\frac {1}{y} \frac {dy}{dx} = \ln{x} +1$$ $$\frac {dy}{dx} =\left( ln(x)+1 \right) x^x.$$

Is there a method to compute the derivative of ${ x }^{ x }$ that does not rely on logarithmic differentiation?

-
Sort of: you can rewrite $x^x$ as $e^{x\ln x}$ and differentiate that. But the computations are essentially identical. – Brian M. Scott Mar 24 '13 at 3:01
Thanks for the comment, I should have thought of that! I'll type up an answer. – Gamma Function Mar 24 '13 at 3:03

Thanks to Brian M. Scott for the comment that led to this solution:

$y={ x }^{ x }={ e }^{ x\ln { x } }\\ \frac { dy }{ dx } =\left( \ln(x)+1 \right) { e }^{ x\ln { x } }\\ \frac { dy }{ dx } =\left( \ln(x)+1 \right) { x }^{ x }\\$

-
Logarithmic differentiation and this one is essentially the same. – fermesomme Jun 13 '13 at 14:42

There's another way that looks like a gross blunder but actually is perfectly correct. I will illustrate it on the more general question, differentiate $y=f(x)^{g(x)}$.

If $g$ were constant, we'd get $f'(x)g(x)f(x)^{g(x)-1}$.

If $f$ were constant, we'd get $g'(x)f(x)^{g(x)}\log f(x)$.

Add these together to get the answer: $$y'=f'(x)g(x)f(x)^{g(x)-1}+g'(x)f(x)^{g(x)}\log f(x)$$

It's easy to see that in the original problem, where $f(x)=x$ and $g(x)=x$, this reduces to $x^x+x^x\log x$, as obtained by other methods.

-
Why did you add them together? – A Googler Jan 18 '15 at 11:06
@AGo, mostly because it works. – Gerry Myerson Jan 18 '15 at 17:24
Yeah , i meant why does it work? – A Googler Jan 19 '15 at 11:24
@AGo, I think it's an application of a version of the chain rule. If $y$ is a function of $s$ and $t$, each of which is a function of $x$, then $dy/dx=(\partial y/\partial s)(ds/dx)+(\partial y/\partial t)(dt/dx)$. Here we have $y=s^t$ with $s=f(x)$, $t=g(x)$. – Gerry Myerson Jan 20 '15 at 0:53
@GerryMyerson: it is an application of the chain rule (no doubt about it) – robjohn Mar 31 '15 at 11:54